2014
DOI: 10.1152/ajpendo.00364.2013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term disruption of maternal glucose homeostasis induced by prenatal glucocorticoid treatment correlates with miR-29 upregulation

Abstract: Excess of glucocorticoids (GCs) during pregnancy is strongly associated with the programming of glucose intolerance in the offspring. However, the impact of high GC levels on maternal metabolism is not clearly documented. This study aimed to test the hypothesis that mothers exposed to elevated levels of GCs might also display long-term disturbances in glucose homeostasis. Dexamethasone (DEX) was administered noninvasively to the mothers via drinking water between the 14th and the 19th days of pregnancy. Mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 70 publications
0
17
0
4
Order By: Relevance
“…Consistent with the present data, we previously reported that pregnant rats treated with dexamethasome present a long‐term sustained reduction in insulin secretion and syntaxin 1a levels, which are correlated with increased miR‐29a levels (Gomes et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with the present data, we previously reported that pregnant rats treated with dexamethasome present a long‐term sustained reduction in insulin secretion and syntaxin 1a levels, which are correlated with increased miR‐29a levels (Gomes et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Analysis of mRNA and miRNA expression was performed as previously described (Gomes et al . ). Briefly, the total RNA was extracted using TRIzol reagent from pools of 200 freshly isolated islets.…”
Section: Methodsmentioning
confidence: 97%
“…Aside from the above, many other miRNAs are involved in pancreatic function, especially insulin secretion (e.g., miR-375 , -184, -33 , -187 , -29a , and -30a ) [28,29,30,31,32,33,34,35,36,37]. For example, although miR-29 is mentioned above in regard to its role in regulating β-cell proliferation, it has also been shown in multiple reports to negatively regulate insulin secretion by directly targeting Stx-1a , a t-SNARE protein involved in insulin exocytosis [31], and Mct1 , which may affect insulin secretion [32].…”
Section: Mirnas and Pancreatic β-Cellsmentioning
confidence: 99%
“…For example, although miR-29 is mentioned above in regard to its role in regulating β-cell proliferation, it has also been shown in multiple reports to negatively regulate insulin secretion by directly targeting Stx-1a , a t-SNARE protein involved in insulin exocytosis [31], and Mct1 , which may affect insulin secretion [32]. miR-124a is increased in type 2 diabetic human pancreatic islets and negatively regulates insulin secretion by directly targeting the GTPase Rab27a [33] and Foxa2 [34], which contribute to β-cell dysfunction in T2DM.…”
Section: Mirnas and Pancreatic β-Cellsmentioning
confidence: 99%
“…Dexamethasone and prednisone/prednisolone show potent immunosuppressive, anti-inflammatory and antiallergic effects, which justify their wide prescription for the treatment of chronic autoimmune diseases, inflammatory diseases, organ transplant rejection, among others [6] . However, chronic exposure to the GCs impairs the normal metabolic homeostasis and causes deleterious adverse effects as demonstrated clinically and experimentally including hyperglycemia, glucose intolerance, dyslipidemia, peripheral insulin resistance, muscle wasting, hepatosteatosis, infertility, growth retardation, cognitive dysfunction, glaucoma, cataracts, topical skin thinning, osteoporosis and diabetes, among others [6][7][8] .…”
Section: Research Highlightmentioning
confidence: 99%